Monitoring Saturation Changes with Ambient Seismic Noise and Gravimetry in a Karst Environment. Issue 1 (3rd May 2018) - Fores, B.; Champollion, C.; Mainsant, G.; Albaric, J.; Fort, A.
Abstract : Core Ideas: Saturation changes can be monitored with ambient seismic noise. We present a new and nondestructive tool to investigate deep and heterogeneous vadose zones. At the site scale, this tool fills the gap between local boreholes and global basin information. Different geophysical datasets can be assimilated for hydrological model calibration. On a heterogeneous karstic site in the Larzac plateau (France), we performed cross‐correlations of ambient seismic noise recorded at two broadband seismometers to obtain daily seismic velocity changes. Rayleigh velocity changes at the 6‐ to 8‐Hz frequency band show variations of ±0.2% over 1 yr. Assuming a simple velocity profile, changes are expected to come from depths of tens of meters. Therefore velocity changes at 6 to 8 Hz were interpreted as induced by water saturation changes. A slow infiltration rate would explain the delay of several months between the rainy season (November) and the minimum velocity (June). Superconducting gravimeter, evapotranspiration, and magnetic resonance sounding (MRS) measurements were then combined with seismic data in one‐dimensional physical simulations. Velocity changes clearly constrain hydrological parameters, like saturated hydraulic conductivity, even if the Biot–Gassmann theory does not explain all of the amplitude observed. Nevertheless, this nondestructive method demonstrates great potential in hydrological model calibration. It overcomes the lack of depth resolution of gravimetry and the lack of temporal resolution of MRS. The combination of ambient seismic noise with gravimetry and MRS could fill the instrumental gap currently existing in hydrology for the study of deep and/or complex critical zones.